(untitled) (Research, Society and Development, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by difficulties in communication, social interaction, and repetitive behavior patterns. Nursing plays a fundamental role in the care of children with autism, offering support, family support, and personalized attention. The objective of this study, conducted through a literature review, was to examine the scientific literature related to nursing care for children with autism. The studies analyzed reveal difficulties related to the lack of professional training, but highlight the importance of humanized care, effective communication with families, and collaboration among different professionals. Continuous training of the nursing team and the adoption of specific care strategies are essential to ensure the inclusion, health, and quality of life of autistic children.